Automatic question & answer generation using generative Large Language Model (LLM) - Hasan, A.S.M Mehedi; Ehsan, Md. Alvee; Shahnoor, Kefaya Benta; Tasneem, Syeda Sumaiya (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.